Kepimpinan Menyebar Dalam Kalangan Pengurus Sekolah - Boon, Yusof; Ahnandan, Lavinia a/p (Office of International Affairs (OIA), 2015)
This study aims to identify the level of understanding, level of distributed leadership practices spread and the relationship between the level of understanding of the level of distributed leadership practices spread among schools management in the district Kota Tinggi. This is because the weakness of the leadership of a teacher cannot effectively lead the organization of the school and the school cannot achieve. Therefore, to improve the quality of school management and reduce the problems encountered in the management of school leaders must use its leadership to spread. A total of 250 school administrators such as professors, teachers, senior administrative assistant, senior assistant co-curriculum and senior assistant student affairs from 83 pilot schools have been involved in Kota Tinggi. The data collection questionnaire was divided into three parts, Part A, namely with regard to the background of the respondents, Part B, which deals with the understanding, Part C concerning practice in the management of primary schools. Data were analyzed using Statistical Package for the Social Sciences version 16.0 (SPSS) was used to obtain the frequency, percentage and min, which will then be presented in tabular form. The results showed that the level of distributed leadership knowledge spread among primary school management at a moderately high level, while the level of distributed leadership practices spread among the primary schools in the management of high level. Correlation analysis also confirms that there is a strong positive relationship between the level of knowledge and distributed leadership practices spread among the management of primary schools in Kota Tinggi district. Finally, some suggestions have been submitted to the relevant authorities as well as actions in future studies.Keywordsâ Distributed Leadership, Schools Management, Quality of School